The contingency of the norm: the monstrum (Itinera, 2023)
What does it really mean to contemplate the “anomalous”, the “malformed”, the “anatomical- monster”? Why and how is it so disturbing? And what is the proper norm and status of the monster? The monster is what shocks, the weird, the eerie. The monster is the uncanny, the “unhomely”, das Unheimliche, to borrow from Freud’s famous expression. It’s the irruption of the improper that threatens the stability of life, as it indicates how the commonness of life itself is a precarious yet contingent state. The monster upsets us because it shows us the contingency of the norm. Based upon this assumption, we shall also touch upon other concepts. These might be: the transvaluation of values, the Einverleibung, the Great Health and the theory of the hopeful monster. It is, in the end, a new form of the same: the individual subtracts itself, therefore, from the individuality of the species, but it does so as to affirm a different same that is absolutely contingent. To borrow again from Deleuze, we might say: a “prodigious”, unexpected turn of the becoming.